2022
DOI: 10.3233/jad-215011
|View full text |Cite
|
Sign up to set email alerts
|

A Biological Index to Screen Multi-Micronutrient Deficiencies Associated with the Risk to Develop Dementia in Older Persons from the Community

Abstract: Background: Low blood status in several nutritional compounds, including long-chain omega-3 fatty acids (LC n-3 PUFA), carotenoids, and vitamin D, have been associated with a higher risk to develop dementia. Nutritional deficiencies may potentiate each other regarding dementia risk; yet the association of multiple nutritional deficiencies with dementia has been little explored. Objective: To develop an index of micronutritional biological status (MNBS) for the screening of multi-micronutritional deficiencies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The 13% of participants with the highest nutrient status index had a four-fold increased chance of developing dementia compared to the 21% with the lowest index scores. 7 Additionally, While this earlier research also demonstrated associations between multiple-nutrient suboptimal statuses and brain aging, direct comparison between results is complicated by differences in components and cut-offs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The 13% of participants with the highest nutrient status index had a four-fold increased chance of developing dementia compared to the 21% with the lowest index scores. 7 Additionally, While this earlier research also demonstrated associations between multiple-nutrient suboptimal statuses and brain aging, direct comparison between results is complicated by differences in components and cut-offs.…”
Section: Discussionmentioning
confidence: 88%
“…To construct the nutrient status index as used in our study, we combined the approaches of Bowman and colleagues 6 and Neuffer and colleagues. 7 This nutrient status index indicates the number of highrisk statuses for three nutrients: homocysteine (as marker of B vitamin status), vitamin D, and n-3 PUFAs. These nutrient biomarkers were selected a priori on the basis of having a plausible mechanism of action in preventing dementia, having proof from observational studies of the beneficial associations between the nutrient biomarker and dementia risk, 2 Figure 1 shows the dose-response associations between the individual nutrient statuses with dementia.…”
Section: Construction Of Nutrient Status Indexmentioning
confidence: 99%
“…Notably, associations between multiple nutrients may potentiate the benefits of an individual nutrient [68]. Neuffer et al, for example, assessed plasma levels of LC n-3 PUFA, 25-hydroxyvitamin D, and carotenoids, indicating a fourfold increased risk of dementia among participants who demonstrated higher index values, indicating potential for mitigating cognitive decline through correction of multinutrient deficiencies [69]. In fact, the LipiDiDiet trial tested the efficacy of a multinutrient supplement in preventing Alzheimer's disease progression, with follow-up results after 36 months, revealing significant long-term improvement in cognitive outcomes, brain atrophy, and disease progression among 81 participants (from an initial pool of 311 randomized subjects) [70].…”
Section: Discussionmentioning
confidence: 99%
“…10 A similar index used in the three-City study was also associated with a higher risk of dementia, with a large effect size. 39,40 Effect sizes can be used to estimate sample size (appendix p 10). Importantly, the magnitude of reported associations in the three-city study was high (ie, stronger than the effect size of APOE ε4 status).…”
Section: Defining Early Nutrition and Metabolic Signatures Of Disease...mentioning
confidence: 99%